A layer-wise formulation for transient response of composite sandwich panel in the exposure of thermal shock loading by considering novel linear and torsional elastic foundation. (1st April 2022) - Huang, Wenhua; Wu, Xiongwei; Amine Khadimallah, Mohamed; Viola, Salvatore
Abstract: In order to present practical ways to decline the adverse effects of thermal shock loading from the perspective of improving structural design, authors of this study put their main focus on the analysis of transient coupled poro-thermo-elastic behavior of the sandwich cylindrical panel under multi-directional initially stresses with functionally graded carbon nanotube reinforced (FG-CNTRC) face-layers and polymeric core resting on novel elastic foundation. With the aid of compatibility conditions, the sandwich structure with three layers are modeled. To guarantee the accuracy of the calculations, authors define the governing equations of the system within the context of the exact three-dimensional form of elasticity theory. Additionally, the Navier approach is employed as the analytical solution to find the response of the simply-supported structure in the content of shear stresses and transverse deflection. Dubner and Abate method is utilized to inverse the Laplace transform in order to determine the time history of the system. Convergence of the stress and deflections of the system with respect to passing time is examined and verified. The parametric study reveals that utilizing each of the CNT scattering patterns through the radial direction of the face-layers is useful for protecting specific proportion of the thickness against the applied thermal shock. Moreover, by tracking the effect of increasing the damper coefficient of the surrounding foundation on the different components of the stress, it is revealed that increasing this factor leads to increase of the transverse shear stress and decrease of the normal shear stress.